Literasi Keuangan Pada Generasi Z - Kazia Laturette; Luky Patricia Widianingsih; Lucky Subandi (Jurnal Pendidikan Akuntansi (JPAK), 2021)
In the era of 2020, there are many offers to make purchases easily and quickly for generation Z, proper financial management is needed for current generation Z, so that they are not tied to consumerism. This research is the result of financial literacy training from students of Citra Berkat High School Surabaya, the researcher wanted to find out whether there were differences in understanding and application of financial literacy after participating in this financial literacy training. This financial literacy training was held for 2 months and was systematic, where students were assessed for their understanding and application. This study used a non-paramteric paired t-test. The research data were collected using a questionnaire distributed before and after the training. Students are given a financial literacy questionnaire according to Chen and Volpe (1998). The results of this study show that after participating in financial literacy training, students' understanding of financial literacy does not differ from that of before training, but on average they have increased understanding. In the application of financial literacy there are differences before and after financial literacy training.